Flexibility in the ambrosia symbiosis of Xyleborus bispinatus - Menocal, Octavio; Cruz, Luisa F.; Kendra, Paul E.; Berto, Marielle; Carrillo, Daniel (Frontiers in Microbiology, 2023)
Ambrosia beetles maintain strict associations with specific lineages of fungi. However, anthropogenic introductions of ambrosia beetles into new ecosystems can result in the lateral transfer of their symbionts to other ambrosia beetles. The ability of a Florida endemic ambrosia beetle, Xyleborus bispinatus, to feed and establish persistent associations with two of its known symbionts (Raffaelea subfusca and Raffaelea arxii) and two other fungi (Harringtonia lauricola and Fusarium sp. nov.), which are primary symbionts of invasive ambrosia beetles, was investigated. The stability of these mutualisms and their effect on the beetle’s fitness were monitored over five consecutive generations. Surface-disinfested pupae with non-developed mycangia were reared separately on one of the four fungal symbionts. Non-treated beetles (i.e., lab colony) with previously colonized mycangia were used as a control group. Xyleborus bispinatus could exchange its fungal symbionts, survive, and reproduce on different fungal diets, including known fungal associates and phylogenetically distant fungi, which are plant pathogens and primary symbionts of other invasive ambrosia beetles. These changes in fungal diets resulted in persistent mutualisms, and some symbionts even increased the beetle’s reproduction. Females that developed on Fusarium sp. nov. had a significantly greater number of female offspring than non-treated beetles. Females that fed solely on Harringtonia or Raffaelea symbionts produced fewer female offspring. Even though some ambrosia beetles like X. bispinatus can partner with different ambrosia fungi, their symbiosis under natural conditions is modulated by their mycangium and possibly other environmental factors. However, exposure to symbionts of invasive beetles can result in stable partnerships with these fungi and affect the population dynamics of ambrosia beetles and their symbionts.